On the statistical and Fourier modelling of robot motion - Tenreiro Machado, J. A. (2000)
A new method for the study and optimization of manipulator trajectories is developed. The novel feature resides on the modelling formulation. Standard system descriptions are based on a set of differential equations which, in general, require laborious computations and may be difficul to analyse. Moreover, the derived algorithms are suited to "deterministic" tasks, such as those appearing in a repetitive work, and are not well adapted to a "random" operation that occurs in intelligent systems interacting with a non-structured and changing environment. These facts motivate the development of alternative models based on distinct concepts. The proposed embedding of statistics and Fourier transform gives a new perspective towards the calculation and optimization of the robot trajectories in manipulating tasks.